Tryptophan Metabolism as Source of New Prognostic Biomarkers for FAP Patients. (November 2019) - Crotti, Sara; Bedin, Chiara; Bertazzo, Antonella; Digito, Maura; Zuin, Matteo; Urso, Emanuele DL; Agostini, Marco
Familial adenomatous polyposis (FAP), a common inherited form of colorectal cancer (CRC), causes the development of hundreds to thousands of colonic adenomas in the colorectum beginning in early adolescence. In absence of a prophylactic surgery, FAP patients almost inevitably develop CRC by the age of 40 to 50. The lack of valuable prognostic biomarkers for FAP patients makes it difficult to predict when the progression from adenoma to malignant carcinoma occurs. Decreased tryptophan (TRP) plasma levels and increased indoleamine 2, 3-dioxygenase 1 (IDO1) and tryptophan hydroxylase 1 (TPH1) enzymatic activities have been associated to tumour progression in CRC. In the present study, we aimed at investigating whether an altered TRP metabolism might also exist in FAP patients. Our results highlighted that plasma levels of TRP and its main catabolites are comparable between FAP patients and healthy subject. On the contrary, FAP patients presented significantly higher TRP levels with respect to high-grade adenoma (ADE) subjects and CRC patients. Obtained data lead us to evaluate IDO1 and TPH1 enzymes activity in the study groups. For both enzymes, it was possible to discriminate correctly between FAP subject and ADE/CRC patients with high sensitivities and specificities. By receiver operating characteristic (ROC) curve analysis, the cut-off values of IDO1 and TPH1 enzymatic activities associated to the presence of an active malignant transformation have been calculated as >38 and >5.5, respectively. When these cut-off values are employed, the area under the curve (AUC) is > 0.8 for both, indicating that TRP metabolism in patients with FAP may be used to monitor and predict the tumorigenic evolution.